Game Analytics and Participatory Efficacy - Chia, Aleena (AoIR Selected Papers of Internet Research, 2017)
This paper investigates the Massively Multiplayer Online Game _EVE Online’s_ system of consumer delegates, who have been elected by fellow players through voting systems created by the game’s commercial developers. MMOGs are continually developed, effectuating changes that have social, political, and economic ramifications for fractious player groups, who vote to have their interests represented to developers. This consumer delegation is part of an ascendant form of democracy because of their legitimation of “datafied” forms of collective self-knowledge that are not aggregated from players’ opinions and choices, but are extracted from game analytics. This paper argues that “representativeness” operates as a boundary object in delegates’ player advocacy and corporate consultancy, in order to provisionally realize the founding vision of co-creation. This is a vision of mutual benefit from relations of increased dialogue, transparency, access, and accountability between consumers and corporations. The interpretive flexibility of “representation” allows delegates to mediate inconsistencies of meaning that reside in the social worlds of players and developers. At the boundary between consumer research and political representation, game analytics provides shared standards of scale and objectivity that synchronizes the goals of corporate efficiency and participatory efficacy: how the collective will of participants translates into changes to game architecture, rules, or content. This study foregrounds the mounting political stakes of algorithmic opacities and information asymmetries as media analytics dominate the way publics come to know and talk about themselves.